PATHOLOGICAL MANDIBULAR FRACTURES: A RETROSPECTIVE STUDY - Rosen Tsolov (Peytchinski Publishing, 2022)
Pathological mandibular fractures occur in regions with previously damaged bone structure due to different etiologies. The purpose of the study is to present a retrospective review of patients with pathological mandibular fractures who passed through the Clinic of Oral and Maxillofacial Surgery of St. George University Hospital, Plovdiv, for the period 2005-2019 and to compare the results with published literature. Material and methods: The study includes1328 patients with pathological fractures of the mandible with different etiology. Data were collected on age, gender, pre-existing bone damage and lesions, history of any interventions of the lower jaw and treatment approach. Results: Patients with pathological mandibular fractures are 5,1% of all patients who passed through the clinic for this period. Two hundred of them are associated with benign or malignant bone tumors, 161 with osteomyelitis, 202 with other causes: third molar extraction, implant placement, osteonecrosis. Conclusion: Pathological mandibular fractures have different etiologies. Diagnosis and treatment of this condition are challenging, and the treatment plan should be decided individually, according to the underlying disease.